2021
DOI: 10.1093/cid/ciab419
|View full text |Cite
|
Sign up to set email alerts
|

Trends Over Time in the Risk of Adverse Outcomes Among Patients With Severe Acute Respiratory Syndrome Coronavirus 2 Infection

Abstract: Background We aimed to describe trends in adverse outcomes among patients who tested positive for SARS-CoV-2 between February and September 2020 within a national healthcare system. Methods We identified enrollees in the national U.S. Veterans Affairs healthcare system who tested positive for SARS-CoV-2 between 2/28/2020 and 9/30/2020 (n=55,952), with follow-up extending to 11/19/2020. We determined trends over time in incide… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 36 publications
4
22
0
Order By: Relevance
“…The adoption of therapeutic corticosteroids, prone positioning to improve oxygenation without mechanical ventilation, and overall adaptation of health care systems to the pandemic have been cited as potential reasons for lower contemporary mortality in the general population. 4 , 5 , 7 , 18 The decrease in use of renal replacement therapy observed in this cohort is consistent with findings from the general population and may reflect changes in the approach to volume management over the course of the pandemic. 19 We observed a decline in the use of mechanical ventilation, despite an increase in the proportion of patients requiring any form of supplemental oxygen.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The adoption of therapeutic corticosteroids, prone positioning to improve oxygenation without mechanical ventilation, and overall adaptation of health care systems to the pandemic have been cited as potential reasons for lower contemporary mortality in the general population. 4 , 5 , 7 , 18 The decrease in use of renal replacement therapy observed in this cohort is consistent with findings from the general population and may reflect changes in the approach to volume management over the course of the pandemic. 19 We observed a decline in the use of mechanical ventilation, despite an increase in the proportion of patients requiring any form of supplemental oxygen.…”
Section: Discussionsupporting
confidence: 83%
“… 1 , 2 , 3 Multiple recent studies of hospitalized adults (general population) with COVID‐19 have reported that mortality has declined substantially since the start of the pandemic in the United States and Europe, from 20% to 25% during March and April 2020 to less than 10% during July through November 2020. 4 , 5 , 6 , 7 The overall decline in mortality has been attributed to various factors including earlier diagnosis due to greater access of testing, improvements in the supportive management, and the potential impact of therapies such as corticosteroids and remdesivir. 4 Whether similar decreases in mortality have occurred in SOTR has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Covariates included in the propensity score model were known to be associated with vaccination and SARS-CoV-2 infection or SARS-CoV-2–related death in the VA population ( 17 , 18 , 20 , 21 ). These included age; sex; self-reported race/ethnicity; urban or rural residence (based on ZIP codes, using data from the VA Office of Rural Health [ 22 ], which uses the secondary rural–urban commuting area for defining rurality); geographic location (categorized according to the 19 Veterans Integrated Services Networks [ 23 ]); and the following comorbid conditions: diabetes, congestive heart failure, chronic obstructive pulmonary disease, and chronic kidney disease, defined by appropriate International Classification of Diseases, 10th Revision, codes ( Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Similar to prior studies, we defined SARS-CoV-2–related death as death from any cause within 30 days of a positive test result or COVID-19 diagnosis ( 17 , 18 , 20 , 21 ). Deaths occurring both within and outside the VA are comprehensively captured in the Corporate Data Warehouse from various VA and non-VA sources, including VA inpatient files, the VA Beneficiary Identification Records Locator Subsystem, U.S. Social Security Administration death files, and the U.S. Department of Defense ( 27 ).…”
Section: Methodsmentioning
confidence: 99%
“…In hospitalized patient, the excess risk of death was ~30% lower in the two semesters after the rst wave. The excess risk of death associated with pandemic wave was rst reported in an Italian study of hospitalized patients [12], and then con rmed by studies of Massachusetts healthcare workers [13], patients of the U.S. Veterans Affairs healthcare system [25], and UK patients [26]. The reasons for this effect could include the initial lack of preparedness of national health systems for pandemic management, the lack of knowledge about the most effective therapies for COVID-19 patients with severe disease, and the possibility that frailer people were more affected at the beginning of the pandemic than the rest of the population.…”
Section: Discussionmentioning
confidence: 89%